Fish Diversity and Catch Composition of Purse Seine Fisheries Across Multiple Fishing Grounds in Weru Village, Lamongan Regency - M Ainul Labib; Tatang Mitra Setia; Nonon Saribanon (Journal of Tropical Biodiversity, 2025)
Purse seine fisheries represent an important component of capture fishing activities conducted by local fishers in Weru Village, Lamongan Regency. However, spatial variations in catch composition and fish diversity across different fishing grounds are still poorly documented. This study aims to analyze fish community structure at four purse seine fishing locations through assessments of catch composition and ecological indices. Data were collected during July–August 2025 through direct observations at landing sites by recording the number of individuals for each species. Analytical procedures included the Shannon-Wiener Diversity Index (H’), Pielou’s Evenness Index (E), and Simpson’s Dominance Index (C) to evaluate community differences among locations. The results reveal clear spatial differences in fish community structure. In total, the purse seine fishery recorded 11 fish species with a total of 15,041 individuals across four fishing locations, indicating a marked disparity in catch abundance across the sites. Locations A and B were dominated by Hilsa kelee, with high catch numbers (3,886 and 7,286 individuals), resulting in low diversity (H’ = 0.18 and 0.06) and high dominance (C = 0.94 and 0.98). In contrast, location D demonstrated a more balanced and stable fish community structure, reflected in its notably higher diversity (H’ = 1.29), high evenness (E = 0.66), and low dominance (C = 0.40). These findings offer important baseline insights to support spatially informed management of small pelagic fisheries in the coastal.